Modeling performance in reverse osmosis wastewater treatment post-trial coke in the integrated systems based on the assumptions of the relaxation model = Modelowanie wydajności procesu odwróconej osmozy w oczyszczaniu poprocesowych wód koksowniczych w układzie zintegrowanym w oparciu o założenia modelu relaksacyjnego - Mielczarek, Karolina; Bohdziewicz, Jolanta; Kwarciak-Kozłowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the results of studies on coking wastewater, coming from the coke plant "Koksownia Czestochowa Nowa" in two integrated systems associating coagulation volume and advanced oxidation with reverse osmosis. The process of coagulation were performed using iron sulfate (III), (PIX 113) of 400 mg/dm3 and wastewater acidity at pH = 9.
Keywords: oczyszczanie ścieków koksowniczych; koagulacja objętościowa; model relaksacyjny; odwrócona osmoza; coking wastewater; volume coagulation; advanced oxidation; relaxation model; reverse osmosis